Effect of creatine monohydrate supplementation on anaerobic performance in elite male basketball players - Balabinis, C.; Poulos, S.; Bizas, G.; Fevga, A. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The purpose of this investigation was to examine the impact of oral long - term creatine monohydrate supplementation on anaerobic power in elite basket - ball players. Conclusions of the study: Long term (8-week period) oral supplementation of creatine monohydrate enhances significantly anaerobic capacity. However, findings in the literature showed that the beneficial effect of creatine on muscle function might disappear, when creatine is continuously ingested for over than two months [2]. Further research is needed to define better its acute and chronic effects on physiological performance.